Combining metal nanoparticles and nanobodies to boost the biomedical imaging in neurodegenerative diseases - Sanna, A.; Quarta, A.; Pieroni, N.; Parodi, B.; Palermo, F.; Bukreeva, I.; Fratini, M.; Massimi, L.; Simeone, D.; Le Guével, X.; Bravin, A.; Quintiero, E.; et al. (Frontiers in Nanotechnology, 2023)
In the study of neurodegenerative diseases, the possibility to follow the fate of specific cells or molecules within the whole body would be a milestone to better understand the complex evolution of disease mechanisms and to monitor the effects of therapies.The techniques available today do not allow the visualization of disease-relevant cells within the whole tridimensional biological context at high spatial resolution.Here we show the results from the first validation steps of a novel approach: by combining the conjugate nanobodies anti-glial fibrillary acidic protein (GFAP) and metal-nanoparticles (i.e. 2 nm gold NP) with X-ray phase contrast tomography (XPCT)we would be able to obtain a tridimensional visualization and identification of cells of interest together with the surrounding tissue and the vascular and neuronal networks.By exploiting the X-ray attenuation properties of metal nanoparticles and the specific targeting capabilities of nanobodies, we could give XPCT the specificity it presently lacks, making it no longer a pure morphological but a molecular and targeted imaging technique.In our case, we synthesized and characterized Gold-NP/GFAP nanobody to target the astrocytes of mouse brain. The results of the first tests presented in this paper have provided us with information on the feasibility of the approach, encouraging us to carry out further experiments in order to achieve the ultimate goal of setting up this new imaging technique.